Republic of Serbia : Second Review Under the Stand-by Arrangement and request for Waivers of Applicability of Performance Criteria-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Serbia's Second Review Under the Stand-by Arrangement (SBA) and Request for Waivers of Applicability of Performance Criteria (PCs). The economy of Serbia is gradually recovering from the 2014 recession, supported by strong export performance coupled with a smaller-than-expected fall in consumption. Inflation has remained below the National Bank of Serbia tolerance band due mainly to low imported inflation. All end-June PCs and indicative targets were met with significant margins. The IMF staff supports the authorities' request for the completion of the Second Review under the SBA, given the program performance so far and the policy commitments going forward.